2011
DOI: 10.1007/s11864-011-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia in soft tissue sarcoma

Abstract: Patients with high-risk soft tissue sarcomas (STS)-FNCLCC grade 2-3, size >5 cm, deep to the fascia-are at risk for developing local recurrence and distant metastasis despite surgical tumor resection. Therefore, the management of high-risk STS requires a multidisciplinary approach. Besides surgery, radiotherapy, and chemotherapy, regional hyperthermia (RHT) has the potential to become the fourth standard treatment modality for the treatment of these patients. RHT means non-invasive selective heating of the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Current approaches to improve the radiotherapeutic outcome of soft tissue sarcomas follow different strategies. These comprise combined-modality treatments with chemotherapy and hyperthermia as well as the implementation of novel irradiation qualities [32][33][34][35]. Whereas for heavy ion irradiation and hyperthermia in combination with photon irradiation the clinical results are promising [33,36], the efficacy of combined radiochemotherapy is controversially discussed and comes at the costs of accumulating side effects [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current approaches to improve the radiotherapeutic outcome of soft tissue sarcomas follow different strategies. These comprise combined-modality treatments with chemotherapy and hyperthermia as well as the implementation of novel irradiation qualities [32][33][34][35]. Whereas for heavy ion irradiation and hyperthermia in combination with photon irradiation the clinical results are promising [33,36], the efficacy of combined radiochemotherapy is controversially discussed and comes at the costs of accumulating side effects [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These comprise combined-modality treatments with chemotherapy and hyperthermia as well as the implementation of novel irradiation qualities [32][33][34][35]. Whereas for heavy ion irradiation and hyperthermia in combination with photon irradiation the clinical results are promising [33,36], the efficacy of combined radiochemotherapy is controversially discussed and comes at the costs of accumulating side effects [37,38]. Additionally, molecularly targeted approaches of radiosensitization with protein kinase, mammalian target of rapamycin (mTOR), and histone deacetylase (HDAC) inhibitors have been developed in preclinical studies and are currently undergoing clinical evaluation [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hyperthermia appears to be a potent modifier of tumor response to radiation and several chemotherapy agents by increasing and targeting their cytotoxic effects in the tumor volume. A multitude of randomized studies showed that hyperthermia combined with radiotherapy, chemotherapy or both, resulted in significant improvement in clinical outcome in cancer patients [1][2][3][4][5][6][7]. The tumor sites include cervix, soft-tissue sarcoma, breast, head and neck, rectum, brain, bladder, lung, esophagus, liver, appendix, prostate and melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia was beneficial when combined with re-irradiation for breast cancer recurrences [5]. For high-risk soft tissue sarcoma, the addition of regional hyperthermia to a multimodal treatment of surgery, radiotherapy, and chemotherapy was shown to improve local recurrence-and disease-free survival [4]. Several randomized trials showed an improvement by adding Biochimica et Biophysica Acta 1853 (2015) [52][53][54][55][56][57][58][59][60][61][62] Abbreviations: ASK1, apoptotic-signaling kinase-1; ATF4, activating transcription factor 4; ATF6, activating transcription factor 6; Bcl-2, B cell lymphoma 2; BiP, binding immunoglobulin protein; cATF6, cleaved ATF6; CHOP, transcriptional factor C/EBP homologous protein; DMEM, Dulbecco's modification of Eagle's medium; DTT, dithiothreitol; eIF2α, eukaryotic translation initiation factor; ER, endoplasmic reticulum; GADD34, growth arrest and DNA damage-inducible 34; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; HeLa, human cervical carcinoma cells; HRP, horseradish peroxidase; Hsp, heat shock protein; IRE1α, inositol-requiring protein-1; JNK, c-Jun N terminal kinase; MOPS, 3-(N-morpholino)-propane sulfonic acid; PBS, phosphate-buffered saline; PERK, protein kinase RNA (PKR)-like ER kinase; PI, propidium iodide; PMSF, phenylmethylsulfonyl fluoride; SDS-PAGE, sodium dodecyl sulphate polyacrylamide gel electrophoresis; SEM, standard error of mean; sXBP1, spliced XBP1; TBP, TATA-box binding protein; TT, thermotolerant; XBP1, X-Box binding protein 1 hyperthermia to radiation for cervical cancer patients, even at 12 years follow-up [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity level of the treatment is unacceptable for clinical practice. But according to the authors' opinion, "regional hyperthermia combined with preoperative or postoperative chemotherapy should be considered as an additional standard treatment option for the multidisciplinary treatment of locally advanced high-grade STS" [44]. This is an extremely doubtful conclusion.…”
Section: The Authors Had Concluded That "Although Improvement Of Lpfsmentioning
confidence: 99%